GIS Web-based South Tangerang City Healthcare Facilities Mapping - Endang Ratnawati Djuwitaningrum; Muhammad Ramli; Muhammad Rizky (Institut Teknologi Indonesia, 2014)
One of the healthcare facilities in South Tangerang City is Puskesmas (Community Health Center).Community Health Center is a functional organization which organizes comprehensive, integrated,equitable, acceptable, and affordable public healthcare. South Tangerang City Health Department has 25 (twenty five) Health Centers which consists of 21 (twenty one) care facility Health Centers, and 4 (four) non-care facility Health Centers. In an effort to provides information to the public about the existence of health center at each district, South Tangerang City Health Department has provided information through the official website which can be accessed at http://dinkes.tangerangselatankota.go.id. Unfortunately the provided information still need to be developed, because from the 25 (twenty five) Health Centers; 12 (twelve) Health Centers only provide information about location and email address, whereas 13 (thirteen) Health Centers provide only limited information about the Health Center address, type of patients served, and types of services provided. This research was develop web based Healthcare Facilities Mapping for South Tangerang City that able to display detail information about Health Centers in interactive presentation using Geographic Information System (GIS) and the Google Maps API (Application Programming interface). In addition beside to provides information about services available at each health center, this application also provides map based navigation to each health center in South Tangerang City.